Comprehensive analysis of the MLH1 promoter region in 480 patients with colorectal cancer and 1150 controls reveals new variants including one with a heritable constitutional MLH1 epimutation. Issue 4 (22nd February 2018) - Morak, Monika; Ibisler, Ayseguel; Keller, Gisela; Jessen, Ellen; Laner, Andreas; Gonzales-Fassrainer, Daniela; Locher, Melanie; Massdorf, Trisari; Nissen, Anke M; Benet-Pagès, Anna; Holinski-Feder, Elke
Abstract : Background: Germline defects in MLH1, MSH2, MSH6 and PMS2 predisposing for Lynch syndrome (LS) are mainly based on sequence changes, whereas a constitutional epimutation of MLH1 (CEM) is exceptionally rare. This abnormal MLH1 promoter methylation is not hereditary when arising de novo, whereas a stably heritable and variant-induced CEM was described for one single allele. We searched for MLH1 promoter variants causing a germline or somatic methylation induction or transcriptional repression. Methods: We analysed the MLH1 promoter sequence in five different patient groups with colorectal cancer (CRC) (n=480) composed of patients with i) CEM (n=16), ii) unsolved loss of MLH1 expression in CRC (n=37), iii) CpG-island methylator-phenotype CRC (n=102), iv) patients with LS (n=83) and v) MLH1-proficient CRC (n=242) as controls. 1150 patients with non-LS tumours also served as controls to correctly judge the results. Results: We detected 10 rare MLH1 promoter variants. One novel, complex MLH1 variant c.-63_-58delins18 is present in a patient with CRC with CEM and his sister, both showing a complete allele-specific promoter methylation and transcriptional silencing. The other nine promoter variants detected in 17 individuals were not associated with methylation. For four of these, a normal, biallelic MLH1 expression was found in the patients' cDNA. Conclusion: We report the second promoter variant stably inducing a hereditary CEM. Concerning the classification of promoter variants, we discuss contradictory results from the literature for two variants, describe classification discrepancies between existing rules for five variants, suggest the (re-)classification of five promoter variants to (likely) benign and regard four variants as functionally unclear.